Effects of the Charge Ions Strength on the Swelling of Organic–Inorganic Nanogels. (22nd June 2016) - Yu, Qin; Lu, Xiangguo; Wang, Jing; Guo, Qi; Niu, Liwei
Abstract : The swelling behavior and swelling mechanism of hydrogels can be greatly affected by the charge strength of ions in them. To investigate such effects, we prepared two gels: a carboxylic acid gel (CAG) and a poly(2‐acrylamide–methyl propane sulfonic acid) gel (SAG) based on starchy polyacrylamide (PAM) nanocomposite gels, both with montmorillonite, which underwent in situ intercalation, and used them as probes in swelling experiments. The equilibrium swelling rates (ESRs) of the hydrogels in both salt water and acidic water strongly depended on the charge strength of the ions in the chains. SAG had a higher ESR than CAG at the same mole ratio of polymer/water, which is attributed to the greater electrostatic repulsion between the strong electrolyte ions of SAG. Both water salinity and hydrogen ion contact of the hydrogels weakened ESR with the enhancement of charge ionic strength. The downward trend of ESR with increasing concentration of salt or hydrogen ions became weaker in SAG compared to CAG, which is attributed to the shielding and deprotonation effects of the strong electrolyte ions. Regarding the swelling mechanism, the chain relaxation occurred in neutral and acidic solutions for SAG and in neutral and weak acidic solutions for CAG, but water diffusion dominated in strong acidic solutions for CAG, leading to different swelling behaviors. Abstract : The swelling behavior and the swelling mechanism of hydrogels can be greatly affected by the charge strength of ions in them. We developed two gels: a carboxylic acid gel (CAG) and a poly(2‐acrylamide‐methyl propane sulfonic acid) gel (SAG) based on starchy polyacrylamide (PAM) nanocomposite gels both with montmorillonite, which underwent in‐situ intercalation, which were used as probes in swelling experiments to investigate such effects. The results showed that the equilibrium swelling rates (ESR) of the hydrogels in both salt water and acidic water strongly depended on the charge strength of the ions in chains. SAG had a higher ESR than CAG at the same mole ratio of polymer/water. The ESRs of hydrogels were decreased with the increasing concentration of salt water. The downward trend of ESR became weaker in SAG compared to CAG. Regarding the swelling mechanism, the chain relaxation occurred in neutral and acidic solutions for SAG and in neutral and weak acidic solutions for CAG but water diffusion dominated in strong acidic solutions for CAG, leading to different swelling behaviors.